EKSPLORASI DAN IDENTIFIKASI BAKTERI SELULOLITIK PADA LIMBAH DADUK TEBU (Saccharum Officinarum L) - Evy Ratnasari Ekawati; Ni’matuzahroh Ni’matuzahroh; Tini Surtiningsih; Agus Supriyanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
This study aims to determine the diversity of cellulolytic bacteria in sugarcane trash (Saccharum offi cinarum L). This study was an explorative research by observing the clear zone in the medium CMC (carboxyl methyl cellulose) with 0.1% congo red. Characterization of cellulolytic bacteria was through by observing the bacterial of colony morphology, cell shape and physiology characteristics. The research datas were analyzed descriptively. From the results of this study, it were obtained six types of isolates that grew well on CMC medium. Based on the characterization of bacteria, six kinds of these isolates belongs to Cellulomonas sp., Cellvibrio sp., Cytophagasp., Micrococcus sp. and Pseudomonas sp. genera.